Inhibition of dengue virus replication by novel inhibitors of RNA-dependent RNA polymerase and protease activities - Sveva Pelliccia; Yu-Hsuan Wu; Antonio Coluccia; Giuseppe La Regina; Chin-Kai Tseng; Valeria Famiglini; Domiziana Masci; John Hiscott; Jin-Ching Lee; Romano Silvestri (Taylor & Francis Group, 2017)
Dengue virus (DENV) is the leading mosquito-transmitted viral infection in the world. With more than 390 million new infections annually, and up to 1 million clinical cases with severe disease manifestations, there continues to be a need to develop new antiviral agents against dengue infection. In addition, there is no approved anti-DENV agents for treating DENV-infected patients. In the present study, we identified new compounds with anti-DENV replication activity by targeting viral replication enzymes - NS5, RNA-dependent RNA polymerase (RdRp) and NS3 protease, using cell-based reporter assay. Subsequently, we performed an enzyme-based assay to clarify the action of these compounds against DENV RdRp or NS3 protease activity. Moreover, these compounds exhibited anti-DENV activity in vivo in the ICR-suckling DENV-infected mouse model. Combination drug treatment exhibited a synergistic inhibition of DENV replication. These results describe novel prototypical small anti-DENV molecules for further development through compound modification and provide potential antivirals for treating DENV infection and DENV-related diseases.